Perbedaan Tingkat Perilaku Agresi Berdasarkan Jenis Kelamin pada Siswa Sekolah Menengah Kejuruan Kota Yogyakarta - Saputra, Wahyu Nanda Eka; Hanifah, Nadiah; Widagdo, Dika Nur (Jurnal Kajian Bimbingan dan Konseling, 2017)
The purpose of this study is to identify whether there are differences between male student aggression behavior and female students aggresive behavior in Yogyakarta. This comparative study involved 160 students from Sekolah Menengah Kejuruan Muhammadiyah in Yogyakarta as a sample. Simple Random Sampling technique were used to choose sample. The instrument used is the scale of aggression behavior. Independent Samples Test were used to analysis the data. The research findings show that there is no significant difference between male student aggression behavior and female students aggresive behavior. This study recommends counseling service to reduce and overcome student aggression behavior.